2021
DOI: 10.3389/fmed.2021.631335
|View full text |Cite
|
Sign up to set email alerts
|

D-Dimer-Driven Anticoagulation Reduces Mortality in Intubated COVID-19 Patients: A Cohort Study With a Propensity-Matched Analysis

Abstract: Objective: Examine the possible beneficial effects of early, D-dimer driven anticoagulation in preventing thrombotic complications and improving the overall outcomes of COVID-19 intubated patients.Methods: To address COVID-19 hypercoagulability, we developed a clinical protocol to escalate anticoagulation based on serum D-dimer levels. We retrospectively reviewed all our first 240 intubated patients with COVID-19. Of the 240, 195 were stratified into patients treated based on this protocol (ON-protocol, n = 91… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
34
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 38 publications
3
34
1
1
Order By: Relevance
“…Retrospective studies have suggested that increasing the dose of prophylactic anticoagulation from a standard dose to an intermediate or therapeutic dose in severe patients may be beneficial [14] , [15] , [16] .…”
Section: Methodsmentioning
confidence: 99%
“…Retrospective studies have suggested that increasing the dose of prophylactic anticoagulation from a standard dose to an intermediate or therapeutic dose in severe patients may be beneficial [14] , [15] , [16] .…”
Section: Methodsmentioning
confidence: 99%
“…The pathology of COVID 19 has an inflammatory and a thrombotic component 2,3,4 . COVID-19 is characterized by distinct changes in hematological, biochemical and radiological findings.…”
Section: Discussionmentioning
confidence: 99%
“…2,3,4,5,6) with their consent. The group consisted of 25 patients in the age group of 19 years to 72 years with an average of 52 years.…”
mentioning
confidence: 99%
“…Given the preponderance of evidence of SARS-CoV2 causing microthrombi and coagulation cascade abnormalities, there is growing evidence that adults infected with SARS-CoV2 can have thrombotic microangiopathy (TMA)-related changes in the kidney [ 33 , 34 ]. A propensity score-matched cohort analysis found anti-coagulation directed therapy to lower d-dimer levels had both lower mortality and AKI rates compared to standard of care [ 35 ]. This may reflect the role of systemic microthrombi as an important driver in COVID-19 complications and mortality [ 35 ].…”
Section: Kidney-specific Sars-cov2 Clinical Manifestationsmentioning
confidence: 99%